Automated Inventory Management with Stock Optimization System - Bera, Sumit Kumar; Pal, Souvik; Kashyap, Vishal; Vishal Kumar; Yachna Raj; Sahana, Sudipta (International Journal of Computer Sciences and Engineering, 2022)
This project is aimed at developing a web-based portal named as automated inventory management with stock Optimization system for handling the stock system of any retail organisation. The stock management with stock Optimization device refers back to the machine and tactics to control the inventory of enterprise. This system can be used to keep the info of the inventory, stock renovation, update the inventory primarily based on the income information, generate income and inventory file each day or weekly based, generating invoice and also sending notification or mail earlier than expiry date of a product for giving it priority. In this system we are solving different problem affecting to sales management and purchase management. Automated Inventory Management with Stock Optimization System is important to ensure quality control in businesses that handle transactions resolving around consumer goods. Without proper inventory control, a large retail store may runout of stock on an important item. A good inventory management with stock optimization system will alert the wholesaler when it is time to record. Inventory Management with Stock Optimization System is also on important means of automatically tracking large shipment. An automated Inventory Management with Stock Optimization System helps to minimize the errors while recording the stock.